Combination of virtual bronchoscopic navigation, endobronchial ultrasound, and rapid on-site evaluation for diagnosing small peripheral pulmonary lesions: a prospective phase II study - Maekura, Toshiya; Sugimoto, Chikatoshi; Tamiya, Akihiro; Saijo, Nobuhiko; Naoki, Yoko; Koba, Taro; Kimura, Yohei; Matsuda, Yoshinobu; Kanazu, Masaki; Takeuchi, Naoko; Sasaki, Yumiko; Naito, Yujiro; et al. (Journal of Thoracic Disease, 2017)
Background: The diagnostic yield of peripheral pulmonary lesions (PPLs) by flexible bronchoscopy (FB) is still insufficient. To improve the diagnostic yield of bronchoscopy, several techniques such as endobronchial ultrasound (EBUS), virtual bronchoscopic navigation (VBN), and rapid on-site evaluation (ROSE) have been examined. The primary purpose of the present study was to evaluate the usefulness of combining EBUS, VBN, and ROSE for diagnosing small PPLs. Methods: Patients with PPLs 30 mm or less on chest computed tomography (CT) were prospectively enrolled. We determined the responsible bronchus for the target lesions using VBN before bronchoscopy was performed. EBUS and ROSE were performed during the examination to determine whether the bronchus and specimen were adequate. On the basis of previous studies, we assumed that the diagnostic yield of 85% among eligible patients would indicate potential usefulness, whereas, the diagnostic yield of 75% would indicate the lower limit of interest. The required number of patients was estimated as 45 for a one-sided α value of 0.2 and a β value of 0.8. The primary study endpoint was the diagnostic yield. Results: Between June 2014 and July 2015, we enrolled 50 patients in the present study, and we excluded 5 patients. The total diagnostic yield of 45 PPLs was 77.7%. In cases of lung cancer, the diagnostic yield was 84.2%. The sensitivity, specificity, positive predictive value, and negative predictive value of ROSE were 90.6%, 92.3%, 96.7%, and 80.0%, respectively. The diagnostic yield of PPLs from 20 to 30 mm was 87.5%, and the diagnostic yield of PPLs less than 20 mm was 66.7%. PPLs for which the probe was located within the lesion had the highest diagnostic yield. Conclusions: We could not demonstrate usefulness for diagnosing small PPLs by combining EBUS, VBN, and ROSE. However, combining these techniques may be useful for diagnosing lung cancer.